Accelerated Atherosclerosis in Rheumatoid Arthritis: Mechanisms and Treatment - Reiss, Allison B.; Silverman, Andrew; Khalfan, Muhammed; Vernice, Nicholas A.; Kasselman, Lora J.; Carsons, Steven E.; De Leon, Joshua (Current Pharmaceutical Design, 2019)
Background: Rheumatoid arthritis (RA) is a chronic systemic autoimmune inflammatory disorder that increases the risk of developing cardiovascular disease. There is accumulating evidence that the RA disease state accelerates the formation of atherosclerotic plaques. Treatments for RA improve joint symptomatology and may reduce inflammation, but consideration of their effects on the cardiovascular system is generally low priority. Objective: Since cardiovascular disease is the leading cause of mortality in RA patients, the impact of RA therapies on atherosclerosis is an area in need of attention and the focus of this review. Results: The drugs used to treat RA may be analgesics, conventional disease-modifying anti-rheumatic drugs, and/or biologics, including antibodies against the cytokine tumor necrosis factor-α. Pain relievers such as nonselective non-steroidal anti-inflammatory drugs and cyclooxygenase inhibitors may adversely affect lipid metabolism and cyclooxygenase inhibitors have been associated with increased adverse cardiovascular events, such as myocardial infarction and stroke. Methotrexate, the anchor disease-modifying anti-rheumatic drug in RA treatment has multiple atheroprotective advantages and is often combined with other therapies. Biologic inhibitors of tumor necrosis factor-α may be beneficial in preventing cardiovascular disease because tumor necrosis factor-α promotes the initiation and progression of atherosclerosis. However, some studies show a worsening of the lipid profile in RA with blockade of this cytokine, leading to higher total cholesterol and triglycerides. Conclusion: Greater understanding of the pharmacologic activity of RA treatments on the atherosclerotic process may lead to improved care, addressing both damages to the joints and heart.
Keywords: atherosclerosis